Complex Case of Open Fracture-Dislocation of the Elbow - Tommy Primeau; Philippe Beauchamp-Chalifour; Stéphane Pelet (Case Reports in Orthopedics)
Complex elbow instability is difficult to surgically address. Careful consideration of the fractures and soft tissue injuries is required. We present the case of a patient who sustained an open fracture-dislocation of the elbow with significant loss of the external humeral condyle and partial loss of the olecranon. He was surgically treated with an iliac crest tricortical autograft fixed with a buttress plate and a lag screw. His lateral ulnar collateral ligament was reconstructed with tendinous autograft collected from his third and fourth extensor digitorum longus tendons. While the procedure complicated with a Nocardia infection and wound breakdown, the patient almost had full range of motion without instability at 11 months of follow-up.